A Trade Potential in the Bilateral Relationship Between Indonesia-South Korea (Perspective: SITC Agregat 1 Digit) 2013-2022 - Nurhidayah, Uci Yusri (Kementerian Luar Negeri Republik Indonesia, 2024)
The Republic of Indonesia and South Korea have engaged in a bilateral cooperation spanning 50 years across diverse domains. Despite the success of this collaboration in augmenting the overall trade between the two nations in alignment with their initial economic objectives, the trajectory of trade development has not consistently followed a linear pattern. This study aims to elucidate the trading dynamics between Indonesia and South Korea from 2013 to 2022. This period was selected as it reflects significant dynamics in bilateral trade relations as well as global economic fluctuations that influenced the trade patterns of both countries. This is achieved through a comprehensive analysis utilizing methodologies such as the Grubel-Lloyd Index, Trade Balance Index (TBI), Trade Complementarity Index (TCI), and Revealed Symmetric Comparative Advantage Index (RSCA). The research outcomes reveal a high degree of industrial interrelatedness within 10 commodity groups, with 7 exhibiting robust integration and 3 displaying varying degrees of integration ranging from moderate to weak. Despite the sustained high level of compatibility in the trade structure, discernible fluctuations are observed in trade surpluses and deficits. The analysis of the Revealed Symmetric Comparative Advantage Index highlights the absence of significant comparative advantages for Indonesia across the majority of the analyzed commodities. Notwithstanding marginal alterations in the Product Mapping classification, statistical analyses of (IIT), TBI, TCI, and RSCA underscore bilateral trade's nuanced and dynamic nature, with annual fluctuations necessitating focused attention.